Women’s leadership in academic medicine: a systematic review of extent, condition and interventions - Alwazzan, Lulu (BMJ Open, 2020)
OBJECTIVES: Because culture reflects leadership, the making of diverse and inclusive medical schools begins with diversity among leaders. The inclusion of women leaders remains elusive, warranting a systematic exploration of scholarship in this area. We ask: (1) What is the extent of women’s leadership in academic medicine? (2) What factors influence women’s leadership? (3) What is the impact of leadership development programmes? DESIGN: Systematic review. DATA SOURCES: A systematic search of six online databases (OvidMEDLINE, EMBASE, CINAHL, PsycINFO, the Cochrane Library and ERIC) from the earliest date available to April 2018 was conducted. Bridging searches were conducted from April 2018 until October 2019. ELIGIBILITY CRITERIA: (1) Peer-reviewed; (2) English; (3) Quantitative studies (prospective and retrospective cohort, cross-sectional and preintervention/postintervention); evaluating (4) The extent of women’s leadership at departmental, college and graduate programme levels; (5) Factors influencing women’s leadership; (6) Leadership development programmes. Quantitative studies that explored women’s leadership in journal editorial boards and professional societies and qualitative study designs were excluded. DATA EXTRACTION AND SYNTHESIS: Two reviewers screened retrieved data of abstracts and full-texts for eligibility, assessment and extracted study-level data independently. The included studies were objectively appraised using the Medical Education Research Quality Study Instrument with an inter-rater reliability of (κ=0.93). RESULTS: Of 4024 records retrieved, 40 studies met the inclusion criteria. The extent of women’s leadership was determined through gender distribution of leadership positions. Women’s leadership emergence was hindered by institutional requirements such as research productivity and educational credentials, while women’s enactment of leadership was hindered by lack of policy implementation. Leadership development programmes had a positive influence on women’s individual enactment of leadership and on medical schools’ cultures. CONCLUSIONS: Scholarship on women’s leadership inadvertently produced institute-centric rather than women-centric research. More robust contextualised scholarship is needed to provide practical-recommendations; drawing on existing conceptual frameworks and using more rigorous research methods.